Trend Perkembangan Ekonomi Digital di Era Industri 4.0 - Muhammad Rizal Arsyad; Dedi Junaedi; Riyanto Riyanto (Comit: Communication, Information and Technology Journal, 2023)
The purpose of this study is to analyze the efforts to develop the HR and innovation ecosystem in the digital economy. The research method used is a qualitative analysis method with a literature study approach. The development of science and technology of mankind has brought us to a new era, the era of technology and information, the digital age. The development of human civilization that has occurred to date has led to progress in various aspects of life, social, economic, cultural, spiritual, technological, and linguistic. The dynamics of digital civilization is also happening in Indonesia. How developed countries build their digital economy ecosystems. It takes a number of examples from progress in developed and neighboring countries. Experience in other countries is a parameter of where Indonesia's current position is. And what are the efforts and targets that Indonesia needs to do in order to become big in the digital economy, especially for the next 5 years? Keywords: new era, digital economic civilization, Indonesia